KESULITAN BELAJAR SISWA DALAM MENYELESAIKAN SOAL CERITA MATERI PERSAMAAN LINEAR SATU VARIABEL DI SMP N 2 AMPEK ANGKEK - Putri Latifa; Isnaniah Isnaniah; Elva Elva (Universitas Pahlawan Tuanku Tambusai, 2022)
Mathematics is a science that has been learned from an early age. But we see that most students think that mathematics is a lesson or something that is scary and difficult to learn. The difficulties experienced by students can be seen in the process of solving mathematical problems. The purpose of this research in general is to find out what are the students' difficulties in solving word problems on the subject matter of a system of one-variable linear equations in class VII of SMP N 2 Ampek Angkek. The research method used in this research is descriptive method. The results of the study concluded that the difficulties experienced by students in solving word problems on the one-variable linear equation material included: (a) Students had difficulty changing everyday sentences on word problems into mathematical sentences correctly; (b) Students have difficulty making mathematical models; (c) Students have difficulty finding ways and steps to answer questions; (d) Students experience difficulties in performing arithmetic operations in algebraic forms. (2) The difficulties experienced by students were caused by several factors including factors originating from the students themselves, namely: (a) Lack of mastery of the material by students; (b) Lack of student persistence in learning; (c) the lack of students getting word exercises; (d) Lack of concentration. Keywords: difficulty, word problems, SPLSV.